Study of Magnesium Homeostasis and Intracellular Compartmentalization in Human Cells by Fluorescent Chemosensors and Synchrotron X-Ray Fluorescence - Sargenti, Azzurra <1986> (Alma Mater Studiorum - Università di Bologna, 2016)
In this study, we investigated the analytical capabilities of DCHQ5, a new fluorescent chemosensor, belonging to the family of diaza-crown-hydroxyquinolines, for the quantitative assessment of total intracellular magnesium content, and its biological applications. We performed a comparative study of DCHQ5 and DCHQ1, the latter being the mother probe of the series, which showed preliminary encouraging results comparable to atomic absorption spectroscopy. We demonstrated that DCHQ5 is able to accurately quantify the total amount of Mg in a very “small” cellular population, by using a simple spectrofluorimetric assay. Furthermore, DCHQ5 demonstrated to be a versatile tool for different applications: its higher intracellular retentions allow to perform cytofluorimetric assays and two-photon confocal microscopy on whole and viable cells; its photochemical characteristic make it excitable in both UV and visible spectra, and the presence of different lifetimes allow to perform fluorescence life time imaging of intracellular Mg. DCHQ5 was also exploited for studying the involvement of magnesium in the commitment of human adipose-derived mesenchymal stem cells (hASCs) with a mixture of hyaluronic, butyric and retinoic acids (HBR). We found that in normal magnesium availability, hASCs precommitment is associated by an increase of total magnesium content during time and by a block in the G2/M phase of the cell cycle. Moreover, our results demonstrated that magnesium deprivation triggers multilineage enrichments of HBR-induced preconditioning of hASCs. The second part of this research was aimed at comparing single cells elemental analysis performed with synchrotron-based fluorescence and cell population analysis carry out by DCHQ5. We exploited innovative techniques of x-ray fluorescence microscopy by using a multimodal approach in order to achieve within the cells the spatial distribution of the concentration of magnesium and fundamental light elements for life. The combination of classical and innovative analytical techniques can shed new light in the comprehension of magnesium homeostasis.